Sensitivity Study of the Propane Dehydrogenation Process in an Industrial Radial Moving Bed Reactor - Chin, S. Y.; Haniif, Prasetiawan; Anwaruddin, Hisyam; Abdullah, Azahari; Ikmal Hisham, Maharon (Taylor's University, 2015)
Modelling and simulation of the propane dehydrogenation reaction is important for predicting an optimum operating condition to maximise the propylene yield. The present study performed the modelling and simulation study of propane dehydrogenation over a platinum based catalyst in radial moving bed reactor(RMBR). First order power law model was used to express the propane dehydrogenation reaction and side reactions. RMBR was discretized into axial and radial directions and theequations of the discretized bed were solved numerically. The kinetic parameters were optimised by comparing the simulation results with plant data. The predicted propane conversion, reactor outlet temperature and coke content deviated less than 5% from the plant data. The validated model was then used for the sensitivity studiesto evaluate the influence of different possible disturbances onthe process. It was found that the reactor inlet temperature was the most influenced parameter to the reactor performance. The maximum propylene yield 30.34% was produced when the WAIT was +10 K, H2/HC was -0.2and Us was +100 kg/hr from the base case